THE PHOTOCATALYST BASED ON COPPER OXIDES OBTAINED BY ELECTROLYSIS - МАКЄЄВА, І. С.; СМІРНОВ, М. О.; ГАЙДАЙ, І. О. (Technologies and Engineering, 2023)
Purpose. Production of highly dispersed oxide materials based on copper oxides by electrochemical synthesis and investigation of their photocatalytic properties. Methodology. Electrolysis was carried out at different temperatures in heat-resistant glass electrolyzers. The cathode and anode were made of copper. A NaCl solution with a content of 280 g/l was used as an electrolyte. The obtained dry product was investigated by chemical and X-ray fluorescence analyses. The verification of photocatalytic properties was carried out on the example of the reaction of the decomposition of the methyl orange dye in an aqueous solution. Findings. A powdery oxide material based on copper oxides was obtained by electrolysis. The parameters of influence on the rate of formation of oxides were studied. The product of electrolysis consists of a mixture of copper oxides (I) and (II), the phase ratio depends on the modes of the process. The photocatalytic degradation of methyl orange is considered as a model system for the functionalization of the obtained powder material for the destruction of environmentally hazardous substances. Originality. A new effective product obtained on the basis of copper oxides. The optimal conditions for product synthesis have been determined. It is shown that electrolysis allows influencing the size and shape of the particles of the obtained product, making a free surface for participation in reactions. Practical value. A product based on copper oxides can be used as an effective photocatalyst. Due to its stability and increased photocatalytic activity, the powdered product can be used for water purification after chemical, pharmaceutical, petrochemical and other industries.